PENGUNAAN KODE BAHASA OLEH GURU DALAM PENGAJARAN BAHASA INGGRIS DI SEKOLAH MENENGAH ATAS - Hamzah, Hamzah (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2008)
This study is aimed at investigating how the English teachers used language codes in their classroom. The findings of the study revealed that the teachers used Indonesian and English interchangeably, and the larger proporsion is English. The teacher made a marked switching when the introduced new information or intructionand unmarked when there was no new information or instruction introduced. The switching also might occur when they translated what they have just said, and when they introduced the interaction particles at the beginning of their utterances.Â  The findings of the study also revealed that the codeswitching in the classroom had pedagogical porposes. The teacher made switching for classroom management, humour, information clarification, understanding enhancedment, and content presentation.Â